Study of association of respiratory viruses in the etiology of acute lower respiratory tract infections in children and correlation with clinical and laboratory features: role of emerging new viruses - Pillai, Swapna K.; Kailas, Lalitha; M., Neziya (International Journal of Research in Medical Sciences, 2023)
Background: Viruses are one of the major causes of childhood pneumonia with the respiratory syncytial virus getting great attention as an important organism for pneumonia. Methods: This cross-sectional study was conducted in the Department of Paediatrics, Sree Gokulam Medical College and Research Foundation, Thiruvananthapuram, Kerala from May 2022 TO November 2022. 119 children admitted with lower respiratory tract infections were included in this study. Symptoms, signs, and investigation reports including PCR and clinical course in the hospital were recorded. Results: 25% of children were in the age group less than 1 year, 52% were between 1-5 years and 23% were above 5 years. Viruses were isolated in 82 patients (68.9%). The main viruses were respiratory syncytial virus (23.5%), boca virus (16.14%), influenza A (7.5%), influenza B (4.2%), meta pneumonia virus (3.3%), and para influenza virus (2.5%). Patients with boca virus infections had a more severe clinical course. Conclusions: Molecular testing with PCR along with clinical and lab parameters will help us to have more insights into the etiology and clinical presentation of respiratory infections in children and help us to do optimum management avoiding unnecessary antibiotic usage.